2017
DOI: 10.1111/auar.12179
|View full text |Cite
|
Sign up to set email alerts
|

SME Reporting in Australia: Where to Now for Decision‐usefulness?

Abstract: This paper develops recommendations for simplified decision-useful SME financial reporting in Australia -a country that has traditionally allowed a wide range of reporting standards to be used by these entities. Drawing on interviews and comment letters from a number of stakeholders, and data from a survey of users of financial statements of non-publicly accountable unlisted entities, we analyse stakeholder arguments for and against SMEs providing less detailed reports, and identify the line items that might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Furthermore, 48% of the respondents indicated that the nature, volume and complexity of disclosure required by MPERS is excessive (Question 6). This is consistent with Handley et al (2018) on the issues of loss of confidential information to competitors as disclosure of too much information to competitors could threaten the sustainability of SMEs.…”
Section: Other Issues In Interpreting and Applying Mperssupporting
confidence: 85%
“…Furthermore, 48% of the respondents indicated that the nature, volume and complexity of disclosure required by MPERS is excessive (Question 6). This is consistent with Handley et al (2018) on the issues of loss of confidential information to competitors as disclosure of too much information to competitors could threaten the sustainability of SMEs.…”
Section: Other Issues In Interpreting and Applying Mperssupporting
confidence: 85%
“…; FERF ; Handley et al. ; Page ). However, most of these studies identify primary users as including insider shareholders (owners and managers), banks, tax authorities and some others (e.g., insurance companies, leasing companies and vendors).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The body of literature examining the information needs of private users is less extensive (e.g., Abdel-Khalik et al 1983;Barker and Noonan 1996;Carsberg et al 1985;FERF 2006;Handley et al 2017;Page 1984). However, most of these studies identify primary users as including insider shareholders (owners and managers), banks, tax authorities and some others (e.g., insurance companies, leasing companies and vendors).…”
Section: User Perceptions Of the Usefulness Of Financial Reportsmentioning
confidence: 99%
“…The purpose of this first open coding pass through the data was to establish whether the interview data could be divided into more than one study based on divergent topic areas discussed during the interviews. This proved to be the case, and the data relating to the requirements of the users of financial reports are reported elsewhere (Handley et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%